Effect of selenized Athyrium multidentatum (Doll.) Ching polysaccharides on TNF/MAPKs/NF‐κB signaling pathways in RAW 264.7 cells. Issue 11 (23rd July 2022) - Shen, Xiaoyan; Wang, Yang; Yin, Kaiyue; Wang, Feng; Miao, Changqing; Sheng, Jiwen; Liu, Dongmei
Abstract: Polysaccharides from Athyrium multidentatum (Doll.) Ching (AMC) were fractionated and selenylated by HNO3 ‐Na2 SeO3 method. Four selenized polysaccharides were synthesized and fully characterized by ICP‐MS, UV, FT‐IR, 1 H NMR, high‐performance gel permeation chromatography, high‐performance liquid chromatography (HPLC), and SEM. Chemical analysis demonstrated that the selenized polysaccharides were composed of mannose (Man), rhamnose (Rha), glucuronic acid (Glc A), glucose (Glc), galactose (Gal), arabinose (Ara), and fucose (Fuc) with different molar ratios and molecular weights. The immunoactivity results showed that the selenized polysaccharides elevated cell proliferation, phagocytic activity, and promoted the production of TNF‐α, IL‐6, IL‐1β, IFN‐γ, IL‐10, NO, and reactive oxygen species in RAW 264.7 cells, indicating marked immune enhancement activities. RT‐qPCR and Western blot assays revealed that the selenized AMC polysaccharides upregulated the expression levels of many key factors involved in TNF, MAPKs, and NF‐κB signaling pathways. TNF/MAPKs/NF‐κB signaling pathways might play crucial roles in the immune function of selenized AMC polysaccharides. Practical applications: Polysaccharide is an essential nutrient in Athyrium multidentatum (Doll.) Ching. The selenized AMC polysaccharide possesses the activities of organic selenium and polysaccharide, making it abroad application prospects in the fields of medicine, food, and cosmetics.